Enhancing Dalbulus maidis (Hemiptera: Cicadellidae) control: an integrated approach combining Cordyceps javanica (Ascomycota: Hypocreales) and insecticides - Poletto, Thaís Berganton (2024)
The corn leafhopper, Dalbulus maidis, stands out as a critical maize pest , damaging the plant by sap extraction, toxic saliva injection, and, above all, transmission of pathogenic agents such as corn stunt spiroplasma (CSS), maize bushy stunt phytoplasma (MBSP), and maize virulence of aerial conidia, blastospores, and submerged conidia of Cordyceps javanica (ESALQ 1296) against D. maidis, analyze the biological compatibility of this fungus with key insecticides for the corn leafhopper, investigate the effectiveness of combining aerial conidia with insecticides, and propose a strategic approach for D. maidis management. To achieve these objectives, virulence assays were conducted with adult corn leafhoppers, along with in vitro tests to evaluate the germination and growth after the exposure of C. javanica to insecticides. Finally, compatibility tests were performed through insect application. Blastospores proved to be the most effective in controlling the corn leafhopper, exhibiting higher mortality rates and a shorter LT50 than other propagules. The C. javanica isolate demonstrated resistance to tested insecticides in spray mixtures. The inclusion of Silwet L-77 enhanced the effectiveness of some insecticides, making it a useful component along with ethiprole. Furthermore, the combination of C. javanica with ethiprole and methomyl exhibited a synergistic and additive effect, significantly increasing D. maidis mortality. These findings provide valuable insights for developing integrated strategies in D. maidis management, considering the effectiveness of microbiological agents and their interaction with insecticides.